Posterior Tibial Loading Results in Significant Increase of Peak Contact Pressure in the Patellofemoral Joint During Anterior Cruciate Ligament Reconstruction: A Cadaveric Study. Issue 5 (April 2021) - Huang, Wenhan; Ong, Michael Tim-Yun; Man, Gene Chi-Wai; Liu, Yang; Lau, Lawrence Chun-Man; Yung, Patrick Shu-Hang
Background: Inappropriate posterior tibial loading and initial graft tension during anterior cruciate ligament (ACL) reconstruction may cause altered patellofemoral joint (PFJ) contact mechanics, potentially resulting in pain and joint degeneration. Hypothesis: PFJ contact pressure would increase with the increases in posterior tibial loading and graft tension during ACL reconstruction. Study Design: Controlled laboratory study. Methods: Nine fresh-frozen, nonpaired human cadaveric knees were tested in a customized jig from 0° to 120° of knee flexion. First, the knee was tested in the ACL-intact state. Second, reconstruction of the ACLs using different posterior tibial loadings and graft tensions were performed. The posterior tibial loading was evaluated at 2 levels: 33.5 and 67 N. Graft tension was assessed at 3 levels: low tension (20 N), medium tension (60 N), and high tension (80 N). Maximum values of peak contact pressure in the medial and lateral patellar facets were compared between ACL-intact and ACL-reconstructed knees. The PFJ kinematics between ACL-intact knees and ACL-reconstructed knees were compared during knee flexion at 30°, 60°, 90°, and 120°. Results: Reconstruction of ACLs with both low and high posterior tibial loading resulted in significant increases of peak contact pressure in the medial (range of differences, 0.46-0.92 MPa; P < .05) and lateral (range of differences, 0.51-0.83 MPa; P < .05) PFJ compared with the ACL-intact condition. However, no significant differences in PFJ kinematics were identified between ACL-reconstructed knees and ACL-intact knees. In ACL-reconstructed knees, it was found that a high posterior tibial loading resulted in high peak contact pressure on the medial patellar side (range of differences, 0.37-0.46 MPa; P < .05). No significant difference in peak contact pressure was observed among the differing graft tensions. Conclusion: In this cadaveric model, ACL reconstruction resulted in significant increases of peak contact pressure in the PFJ facet when compared with the ACL-intact condition. A high posterior tibial loading can lead to high medial PFJ peak contact pressure. Graft tension was found to not significantly affect PFJ contact pressure during ACL reconstruction. Clinical Relevance: An excessive posterior tibial loading during ACL reconstruction resulted in increased PFJ contact pressures at time of surgery. These data suggest that a low posterior tibial loading might be preferred during ACL reconstruction surgery to reduce the PFJ contact pressure close to that of the ACL-intact condition.